Implementasi Kultur Literasi Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SD Negeri 1001 Batang Bulu Kecamatan Barumun Selatan - Nilam Santika; Siregar, Nurhayati; Rizki Hamdan Saputra (Yayasan Perguruan Kampus, 2023)
In the world of education, there is a lot to be learned by students. The first basic lesson is reading, where reading is a window to the world that can give us broad insight. Therefore, it is important for students to have reading skills. This study uses a class action research method (PTK). Data collection techniques in this study were obtained through observation, documentation and tests. And data analysis techniques in this study using qualitative and quantitative analysis. Based on the results of the actions that the researchers have taken, it can be concluded that through the implementation of literacy culture, it can create an active classroom environment and increase students' understanding. The role of this media is also an important one because it can develop the level of critical thinking in students and improve the quality of the educational process. Implementation of a literacy culture can strengthen the ethical movement and understand information critically and creatively.